ミズホ キチ ト ドームフジ キチ ニ オケル フブキ カンソク - 西村, 浩一; ニシムラ, コウイチ; 亀田, 貴雄; カメダ, タカオ; Nishimura, Kouichi; Kameda, Takao (2008)
P(論文) 2000年9月から11月にかけて,南極みずほ基地において雪粒子の運動と風の乱流構造に着目した吹雪観測を実施した.観測は30mタワーにスノーパーティクルカウンター(SPC)を4台(設置高: 9.6m,3.1m,1.0m,0.2m),超音波風向風速計を3台(設置高: 25m,1.0m,0.2m),気温・露点計を2台(設置高: 3.0m,1.0m)設置して行われた.観測期間中,すべての機器はほぼ順調に作動し,吹雪フラックスの鉛直分布や雪粒子の粒径分布などを風速(摩擦速度)の関数として求めることに成功した.またSPCが降雪の観測にも有用であることが確認されたため,2002年2月から2003年1月にかけては,ドームふじ基地においても観測が行われた. Blowing snow observations were carried out at Mizuho Station, Antarctica from Sept. to Nov. 2000. A blowing snow observation system including snow particle counters (SPC) which can sense not only the number of snow particles but also their diameters, was situated on a 30m tower. All instruments worked properly and the data obtained revealed profiles of mass flux and particle size distributions as a function of the friction velocity. Since the SPC is found to be useful to evaluate precipitation as well, it was set at Dome Fuji Station from Feb. 2002 to Jan. 2003, and measurements of snowfall as well as blowing snow were undertaken. departmental bulletin paper